Genome-first approach to rare EYA4 variants and cardio-auditory phenotypes in adults - Shadi Ahmadmehrabi; Binglan Li; Joseph Park; Batsal Devkota; Marijana Vujkovic; Yi-An Ko; David Van Wagoner; W.H. Wilson Tang; Ian Krantz; Marylyn Ritchie; Jason Brant; Michael J. Ruckenstein; et al. (Human Genetics, 2021)

An assessment of the potential impacts of climate change on freshwater habitats and biota of Indiana, USA - Tomas O. Höök; Carolyn J. Foley; Paris Collingsworth; Leslie Dorworth; Brant Fisher; Jason T. Hoverman; Elizabeth LaRue; Mark Pyron; Jennifer Tank (Climatic Change, 2020)

Estimates of Natural Selection in a Salmon Population in Captive and Natural Environments - MICHAEL J. FORD; JEFFREY J. HARD; BRANT BOELTS; ERIC LaHOOD; JASON MILLER (Conservation Biology, 2008)
Captive breeding is a commonly used strategy for species conservation. One risk of captive breeding is domestication selection—selection for traits that are advantageous in captivity but deleterious in the wild. Domestication selection is of particular concern for species that are bred in captivity for many generations and that have a high potential to interbreed with wild populations. Domestication is understood conceptually at a broad level, but relatively little is known about how natural selection differs empirically between wild and captive environments. We used genetic parentage analysis to measure natural selection on time of migration, weight, and morphology for a coho salmon ( Oncorhynchus kisutch ) population that was subdivided into captive and natural components. Our goal was to determine whether natural selection acting on the traits we measured differed significantly between the captive and natural environments. For males, larger individuals were favored in both the captive and natural environments in all years of the study, indicating that selection on these traits in captivity was similar to that in the wild. For females, selection on weight was significantly stronger in the natural environment than in the captive environment in 1 year and similar in the 2 environments in 2 other years. In both environments, there was evidence of selection for later time of return for both males and females. Selection on measured traits other than weight and run timing was relatively weak. Our results are a concrete example of how estimates of natural selection during captivity can be used to evaluate this common risk of captive breeding programs.